2011
DOI: 10.1016/j.jmoldx.2011.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Mutation Analysis of SLC26A4 for Pendred Syndrome and Nonsyndromic Hearing Loss by High-Resolution Melting

Abstract: Pendred syndrome and DFNB4 (autosomal recessive nonsyndromic congenital deafness, locus 4) are associated with autosomal recessive congenital sensorineural hearing loss and mutations in the SLC26A4 gene. Extensive allelic heterogeneity, however, necessitates analysis of all exons and splice sites to identify mutations for individual patients. Although Sanger sequencing is the gold standard for mutation detection, screening methods supplemented with targeted sequencing can provide a cost-effective alternative. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 51 publications
0
12
0
1
Order By: Relevance
“…However, autoimmune thyroid disease could also be a possibility in some of these patients. At present, Sanger sequencing is the standard for SLC26A4 molecular diagnosis, but other efficient methods such as high-resolution melting are available (4). Development of next-generation sequencing for molecular diagnosis is expected to reduce the utility of methods such as APEX, which here (besides screening for common SLC26A4 mutations) was used to establish whether the HI, alternatively, could be explained by other genes.…”
mentioning
confidence: 99%
“…However, autoimmune thyroid disease could also be a possibility in some of these patients. At present, Sanger sequencing is the standard for SLC26A4 molecular diagnosis, but other efficient methods such as high-resolution melting are available (4). Development of next-generation sequencing for molecular diagnosis is expected to reduce the utility of methods such as APEX, which here (besides screening for common SLC26A4 mutations) was used to establish whether the HI, alternatively, could be explained by other genes.…”
mentioning
confidence: 99%
“…Present study was undertaken for the first time to screen the genetical variants in SLC26A4 gene, if any, in association with nonautoimmune and noncongenital hypothyroidism, which was devoid of any characteristics of Pendred syndrome. The alterations in SL-C26A4 gene are mostly associated with Pendred syndrome or congenital hypothyroidism [24][25][26][27][28][29]32]. However, none of the patients enrolled in this study were registered with any possible sign of Pendred syndrome and/or congenital hypothyroidism, which specify that whatever the genetical alteration noted in this study, they are not associated with Pendred syndrome and/or congenital hypothyroidism; rather might be related with the hypothyroidism detected in adulthood.…”
Section: Discussionmentioning
confidence: 80%
“…And our results demonstrated that HRM is a reliable method for genotyping ALDH2 rs671. Besides genotyping, HRM was also used for gene scanning and methylation analysis [ 14 , 15 ]. One current limitation of HRM is the possibility that another unexpected SNP interferes in the target SNP.…”
Section: Discussionmentioning
confidence: 99%